(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The purpose of the search definition on factors superior this whoever impact on the improvement the exploitation decision this detect on stock exchange markets assumption , and using questioners to data accumulate and the Iraq market of financial papers battleground to search annoy chose the eyeball extension (47) peoples from peoples employees on the market , and using the bought statistic program (SPSS) on input and analysis search data , and machinate the search outputs to their group of factors internal and external which impact on exploitation decision on financial papers markets , and the search commend on necessary rise the incumbency direction in the stock exchange Iraq markets the give information total that are contingent to help investment on the exploitation decision this detect.